2010
DOI: 10.1084/jem.20092017
|View full text |Cite
|
Sign up to set email alerts
|

Antigen persistence and the control of local T cell memory by migrant respiratory dendritic cells after acute virus infection

Abstract: Acute viral infections induce robust adaptive immune responses resulting in virus clearance. Recent evidence suggests that there may be depots of viral antigen that persist in draining lymph nodes (DLNs) after virus clearance and could, therefore, affect the adaptive immune response and memory T cell formation. The nature of these residual antigen depots, the mechanism of antigen persistence, and the impact of the persistent antigen on memory T cells remain ill defined. Using a mouse model of influenza virus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
169
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(189 citation statements)
references
References 41 publications
(100 reference statements)
20
169
0
Order By: Relevance
“…It is thus tempting to speculate that the capability of CD8 + T cells to respond to a short Ag pulse might reflect transient viral gene transcription and its preferred feeding of the class I pathway. The fact that CD4 + T cells respond much longer to residual Ag following viral clearance than CD8 + T cells do also indicates that antiviral CD8 + T cell responses depend on viral transcription (79,80).…”
Section: Discussionmentioning
confidence: 99%
“…It is thus tempting to speculate that the capability of CD8 + T cells to respond to a short Ag pulse might reflect transient viral gene transcription and its preferred feeding of the class I pathway. The fact that CD4 + T cells respond much longer to residual Ag following viral clearance than CD8 + T cells do also indicates that antiviral CD8 + T cell responses depend on viral transcription (79,80).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reasonably assumed that the genetic information of the virus is somehow preserved in the host, and its continued expression at a low level is responsible for this persistence. Indeed, viral transcripts have now been detected long after the virus has been cleared; nonetheless, the antigen appears to persist immunologically even longer after such transcripts cease to be detectable (8). Thus, the molecular basis of antigen persistence has remained mysterious.…”
Section: Discussionmentioning
confidence: 99%
“…This is true for chronically infecting viruses, such as the respiratory syncytial (1,2) and Sendai viruses (3), as well as lytic influenza viruses (4)(5)(6)(7)(8). The evidence that antigens persist comes from immunologic rather than biochemical studies: typically, it has been shown by the ability of the host, which has cleared the infection and in which no antigen is detectable, to readily support stimulation of adoptively transferred naïve T cells for weeks after the infection has been cleared.…”
mentioning
confidence: 99%
See 2 more Smart Citations